(untitled) (Revista de Ciências Agroveterinárias, 2017)
Swine production in Santa Catarina is remarkable because of both the large number of animals as well as the high volume of swine slurry (DLS) generated. The DLS has fertilizer value, but its excessive or improper use can pollute surface and groundwater as well as contribute to the emission of greenhouse gases. An experiment was carried out in the Santa Catarina plateau to evaluate the incorporation into the soil and the addition of nitrification inhibitor as ways to increase the efficiency of DLS and mineral fertilizer (NPK) as sources of nitrogen (N) and other nutrients for corn. The treatments were the DLS and NPK fertilizers, the presence and absence of dicyandiamide (DCD), a control and the surface (Sup) or incorporated (Inc) applications and were arranged in a randomized block design with split plots and four replicates. The incorporation of fertilizer increased the N content in leaves, shoot dry matter and grain yields and the accumulation of N and K in the dry matter and P in corn grain. The DCD in general did not affect grain yield, except in superficial application of the DLS where their presence increased the yield compared to its absence. The DLS and mineral NPK fertilizers have similar efficiency that increases with incorporation into the soil compared to the surface application.